Man is the first way of the Church in the teaching of John Paul II - Kosiorek, Grzegorz (Studia Teologiczne Białystok Drohiczyn Łomża, 2021)
Thanks to His genuine holiness and concern for every human life, John Paul II became a credible witness of Jesus Christ. As a result, His teaching was thoroughly convincing and drew human hearts to follow the path of faith. From an early age, He was very sensitive to the need to help every person, especially the weak and defenseless, who alone cannot face the threats lurking in his or her safety and life. The human person became for Him a determinant pointing the direction in which the Church should go. Observing His life and teaching, we can see that He was concerned with all the important matters that struggles today’s world. He did not shy away from difficult challenges and questions. Although 16 years have passed since the death of the Polish Pope, His teaching is still relevant and can inspire every man of good will to reflect on the passing of time, the meaning of life and the necessity of devotional service to others.